Multimedia Presentation Integrating Interactive Media Produced in Real Time with High Performance Processing - Viel, Caio César; Melo, Erick Lazaro; Godoy, Arthur Pedro de; Dias, Diego R. C.; Trevelin, Luis Carlos; Teixeira, Cesar A. C. (Proceedings of the Brazilian Symposium on Multimedia and the Web (WebMedia); 2012: Proceedings of the 18th Brazilian Symposium on Multimedia and the Web, 2012)
Sophisticated interactive animation may be an interesting element to compose a multimedia document. However, potential demand for high performance computing can make this option impractical in digital interactive TV and mobile device environments, due to computing power restrictions of these platforms. In previous work we proposed a solution to overcome such restrictions based on video streaming. Moving forward the solution, it is described in this paper how to take advantage of media-agnostic characteristic, when present in the multimedia presentation machine, to manage this new type of media in multimedia documents. As a proof of concept we extended and tested an NCL presentation engine to add suport to this new type of media.